Problematika Prinsip Syura dalam Sistem Pemerintahan di Indonesia - Cahyanti Febrianty; Kayla Zulkhaira Sembiring; Kurniati Kurniati (CV. ITTC INDONESIA, 2026)
This study discusses the problems of the shura principle in the governmental system in Indonesia. The principle of shura as a concept of deliberation in Islam has relevance to the democratic system implemented in Indonesia, particularly in decision-making processes that prioritize public participation. However, the implementation of the shura principle in governmental practices still faces various challenges, such as the dominance of political interests, oligarchic practices, weak representation of public aspirations, and the lack of orientation toward public welfare. This study aims to analyze the existence, implementation, and impact of the application of the shura principle in the Indonesian governmental system. The research method used is normative legal research with conceptual and statutory approaches. Data sources were obtained from the Qur’an, hadiths, legislation, as well as literature and scientific journals related to siyasah syar’iyyah and the Indonesian governmental system. The results show that the principle of shura has substantially been reflected in the Indonesian democratic mechanism, especially through representative deliberation and public participation. Nevertheless, its implementation has not run optimally due to the interests of political elites, corruption practices, and weak ethical values in governance. This condition has resulted in declining public trust in the government and the failure to establish a just government oriented toward public welfare. Therefore, strengthening the values of shura in the governmental system is necessary through increasing transparency, accountability, and public participation in policy-making processes.